Factors associated with knowledge in African immigrants with personal experiences of dementia - Manka Nkimbeng; Truphosa (Posa) Aswani; Elle Albers; Wynfred N. Russell; Tetyana P. Shippee; Joseph E. Gaugler (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Dementia literacy shapes understanding of care and caregiving and thus influences the health outcomes of the care partner and the person living with dementia. METHODS Linear regression models were used to identify factors associated with dementia knowledge among a cross‐sectional sample of African immigrants with personal experiences of dementia. RESULTS Among 191 participants, the mean age was 36 (± 13.8) years, 64% were male, and 81% were care partners. Second‐generation African immigrants had statistically significant higher knowledge about dementia causes (4 ± 1.5 vs. 3.5 ± 1.6). Participants who would seek care at health organizations and community networks had higher dementia knowledge compared to those who would seek care at community networks alone (b: 1.23 95% confidence interval [0.25, 2.21]). DISCUSSION Where an African immigrant would seek care was associated with dementia knowledge. Thus, incorporating community care preferences and community‐based approaches into national programs such as the Healthy Brain Initiative, can enhance dementia outreach efforts. Highlights Effective use of community engagement with Africans to explore current dementia knowledge. Second‐generation African immigrants may have more dementia knowledge. African immigrant caregivers may have more dementia knowledge. African immigrants who seek community care only have limited dementia knowledge.